INDONESIA'S GOOD FAITH PRINCIPLES IN INTERNATIONAL ARBITRATION AND GOOD GOVERNANCE IN NATIONAL INVESTMENT - Ary Simanjaya (Jurnal Impresi Indonesia, 2025)
Republic of Indonesia as a country open for investor who want to invest, this shown through Indonesia's willingness to bound by Bilateral Investment Treaty (BIT) with related countries and agreements require investment in Indonesia. Indonesian Government act towards the presence foreign investors is intended, so there's no discrimination against domestic investor through investment law, other law related to investor business, and agreements between countries as basis investment in Indonesia. Behind of Indonesia's welcoming and openness to foreign investment, Republic of Indonesia has faced the Internationale Centre for Settlement of Investment Disputes (ICSID) trial for seven times with varying results each case. Therefore, this study aims to evaluate and analyze attidute Republic of Indonesia in ICSID arbitration trial through all case Indonesia has gone through, by looking at the trial. The results of the study show Indonesia's progressive attitude in responding and providing to ICSID board as Indonesia Government play a real role in the presence of foreign investment, and is adaptive to the principles of the ICSID trial. Further evaluation needed regarding the validity of ICSID membership both in terms of the system and implementation Indonesia can obtain real benefits as an ICSID member in future arbitration proceedings.